THE EFFECT OF THE USE OF THE DURUS AL-LUGAH AL-'ARABIYYAH 'ALA AL-TARIQAH AL-HADISAH BOOK ON LANGUAGE SKILLS AT DARUL HUFFADH TUJU-TUJU ISLAMIC BOARDING SCHOOL KAJUARA BONE - Setiawan, Syarif Agus; Usman, Syahruddin; Haniah, Haniah (Jurnal Diskursus Islam, 2022)
This study aims to analyze whether there is an effect of using the book of Durus al-Lugah al-'Arabiyyah 'ala al-Tariqah al-Hadisah on language skills. It investigated the students in the first grade at Darul Huffadh Tuju-tuju Islamic Boarding School Kajuara Bone. This study was a quantitative research with an Expost Facto approach by collecting and simplifying the data collected using the SPSS application in processing the data. There were two variables in this study, namely the use of the Durus al-Lugah book as a variable (X) and language skills as a variable (Y). While the population in this study was 299 students of KMI in the first grade and the sample was 20% of the population, namely 60 students. The data collection method used questionnaires, tests, documentation and observation. The data analysis used descriptive and inferential statistical analysis. The study results indicate that (1) The use of the Durus al-Lugah al-'Arabiyyah 'alaal-T}ariqah al-Hadisah book in the first grade at Darul Huffadh Tuju-tuju Islamic Boarding School Kajuara Bone is quite significant with a percentage of 65%. (2) Arabic language skills of The first grade students at Darul Huffadh Tuju-tuju Islamic Boarding School Kajuara Bone were quite good, with a percentage of 55%. (3) There was an effect of Variable X on Y in this study. The value of the variable hypothesis test, such as the value of t count, is 6.573, and the value of sig is 0.000. Thus T count is 6.573 > T table 2.00, and Sig 0.00 <0.05 = H1 is accepted. It meant that there was a positive influence and the significance of Durus al-Lugah al-'Arabiyyah 'ala al-Tariqah al-Hadisah on the Language Skills of the first grade KMI students at Darul Huffadh Tuju-tuju Islamic Boarding School Kajuara Bone. If there was no variable Durus al-Lugah al-'Arabiyyah 'ala al-Tariqah al-Hadisah then the students' language skills were -0.945. Then, the value of b (Variable X/Durus al-Lugah al-'Arabiyyah 'ala al-Tariqah al-Hadisah) was 0.266. It indicated that with every 1% addition in the learning effectiveness of using Durus al-Lugah al-'Arabiyyah 'alaal-Tariqah al-Hadisah book, the students' Arabic skills would increase by 0.266 with a percentage value of 42.7%. It means that variable X affects Variable Y. Based on the results of this study, it is hoped that PPDH (Islamic Boarding School Darul Huffadh) will maintain the use of the Durus al-Lugah al-'Arabiyyah 'ala al-T}ariqah al-Hadisah book because it is a structured and systematic book on its theme. It is very suitable for beginners who are new to Arabic and are required to be able to master Arabic as a daily language. It will be optimal if the teachers practice reasonable teaching procedures and use every medium to help the students discover the book's contents and assist the teacher in delivering the material.